Critical evaluation of predictive modelling of a cervical disc design - De Jongh, Cornel (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2007.